International cuisine - Nenes, Michael F. (New Jersey : Wiley & Sons, Inc., 2009)
The Best Tool for Learning About the Diversity of Cuisine from Around the World. Increasing world travel, changing demographics, multinational business, and greater diversity at home have whetted our appetites for international flavors--whether in national dishes or creative culinary fusions. Anyone entering the foodservice industry today must be prepared to meet this growing demand. Taste truly has gone global. With its comprehensive approach, International Cuisine explores countries and regions, cultures, and ingredients, and describes the crucial role they play in different world cuisines.
Mexico -- South America -- The Caribbean -- Japan -- China -- Korea -- Southeast Asia -- Spain -- The Middle East -- Turkey, Greece, and Crete -- Africa -- India -- The British Isles -- France -- Italy -- Germany, Austria, and Switzerland -- Scandinavia and Russia.
Includes index.
Keywords: COOKERY, INTERNATIONAL